Research on Self-collimation Full-scale Angle Measurement Method Based on Composite Biaxial and Combined Target. Issue 1 (1st December 2022) - Li, Kun; Cao, Guohua; Ding, Hongchang; Hou, Han
Abstract : In order to solve the problems such as the limited field of view of traditional self-collimation detection, the inability to achieve continuous detection of 0 360° full circumference and the existence of zero drift in self-collimation measurement. The positive and negative rotation of the inner and outer axes of the dual-axis turntable is used to realize high-precision continuous angle measurement with the autocollimator as the angle reference, and the combination of the compensation target and the fixed target is used to realize the closed-loop compensation of the drift of the autocollimator. The results show that: the repeatability error of the system is 0.05", and the detection accuracy of the system reaches 1.64". On the premise of ensuring the stability of the self-collimation angle reference, the self-collimation full-scale small angle measurement is realized.